Boganmeldelser - Dan Frände; Peter Garde; Vojko Fajgelj; Margaretha Järvinen; Britta Kyvsgaard; Beth Grothe Nielsen; Helén Örnemark Hansen; Sysette Vinding Kruse; Peter Garde; Peter Kruize; Jacob Hilden Winsløw; Paul Larsson; et al. (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews